2019
DOI: 10.1590/0034-7167-2018-0526
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of infusion pumps to reduce errors in a Pediatric ICU

Abstract: Objective: To analyze cost-effectiveness and to calculate incremental cost-effectiveness ratio of the use of infusion pumps with drug library to reduce errors in intravenous drug administration in pediatric and neonatal patients in Intensive Care Units. Methods: Mathematical modeling for economic analysis of the decision tree type. The base case was composed of reference and alternative settings. The target population was neonates and pediatric patients hospitalized in Pediatric and Neonatal Intensive Care Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…As for the cost-effectiveness studies between the use of infusion pumps with drug libraries and conventional infusion pumps to reduce adverse events, it was shown that although the latter has the lowest cost, it also has less effectiveness. 13 The smart pumps infusion pump has software in which a drug library is installed. Connected to the Internet, this system runs scheduled and established applications, and promotes modes of analysis of the collected data.…”
Section: Resultsmentioning
confidence: 99%
“…As for the cost-effectiveness studies between the use of infusion pumps with drug libraries and conventional infusion pumps to reduce adverse events, it was shown that although the latter has the lowest cost, it also has less effectiveness. 13 The smart pumps infusion pump has software in which a drug library is installed. Connected to the Internet, this system runs scheduled and established applications, and promotes modes of analysis of the collected data.…”
Section: Resultsmentioning
confidence: 99%
“…lww.com/JPS/A612). The studies were conducted in the United States (n = 16), [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] the United Kingdom (n = 7), [63][64][65][66][67][68][69] Australia (n = 3), [70][71][72] Brazil (n = 3), [73][74][75] Spain (n = 3), [76][77][78] Mexico (n = 2), 79,80 Saudi Arabia (n = 2), 81,82 Singapore (n = 2), 83,84 Canada (n = 1), 85 China (n = 1), 86 France (n = 1), 87 Germany (n = 1), 88 Italy (n = 1), 89 Netherlands (n = 1), 90 and Switzerland FIGURE 2. Outline of the narrative review process, analysis of the included articles (n = 63), and comparison to our previous systematic reviews.…”
Section: Description Of Studies Exploring Systemic Defenses To Preven...mentioning
confidence: 99%
“…91 Some studies (n = 2) were carried out in multiple countries. 92,93 The studies were conducted in hospital settings without a specification of a specialty area (n = 10), 55,56,[61][62][63]66,73,76,82,90 adult ICU (n = 9), 49,50,52,69,75,[78][79][80]92 hospital pharmacy (n = 7), 47,51,[57][58][59][60]93 pediatric intensive care unit (n = 5), 65,68,72,74,77 pediatric hospital (n = 3), 54,64,71 emergency department (n = 2), 70,84 anesthesia department (n = 1), 87 cancer hospital (n = 1), 86 and pediatric emergency department (n = 1). 81 Some studies (n = 8) were carried out in simulated environments comprising an anesthesia setting (n = 2), 83,88 hospital setting (n = 2), 48,67 ICU (n = 1), 85 NICU (n = 1), ...…”
Section: Description Of Studies Exploring Systemic Defenses To Preven...mentioning
confidence: 99%
See 1 more Smart Citation
“…In these situations, the nurse's quick thinking and technical ability make all the difference when dealing with a patient with several injuries. 5 In this sense, to systematize the care given to patients in the emergency room, we have the Nursing Process (NP), which guides nurses' work, aiming to qualify it. 6 It is a methodological approach used by nurses to provide individualized care to users, whose use has a positive effect on the results of the care given to patients.…”
Section: Introductionmentioning
confidence: 99%